Literatur Review: Compound Content and Bioactivity of Red Algae Found in Indonesia - Nursafira, Salis; Candra Wulan, Mustika; Fitriani Abubakar, Andi Nur (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Red algae are lowland plants that often grow attached to certain substrates such as coral, mud, sand, rocks and other hard objects. This study aims to determine the content of secondary metabolite compounds and bioactivity and types of red algae species in Indonesia by taking references from previous studies. The results obtained are that red algae contain secondary metabolite compounds of steroids and triterpenoids and contain bioactivity such as antibacterial, antiviral, anticancer, antioxidant, anticoagulant, anti-inflammatory, antidiabetic, antiallergic, and analgesic and there are 14 species of red algae in Indonesia including Bostrychia tenella, Bostrychia radicans, Bostrychia sp., Chondria sp., Laurencia sp., Polysiphonia sp. Caloglossa leprieurii, Caloglossa monostica, Gelidium crinale, Gelidium sp., Catenella caespitosa, Catenella nippae, Catenella sp. and Murrayella sp.